Effects of computer-generated music on human physiological, metabolic and endocrine responses. (2016) - Hanson, Petra; Ko, David; Ko, Andrew; Ali, Asad; Kumar, Sudhesh; Spero, Ian; Barber, Thomas M.
To explore effects of program-generated music on physiological, metabolic and endocrine responses. Five healthy males underwent whole-body calorimetry using a standard protocol on three separate days, with no music on day 1 (D1), and genre-specific music from online computer-generated program on days 2 (D2: random track selection) and 3 (D3: track selection based on subject-inputted mood). Measurements included pulse, blood pressure (BP), and blood samples for serum cortisol. A p-value ≤ 0.05 was considered significant. Compared with D1, overall metabolic rate during D2 and D3 was reduced by 54.7 kcal (p = 0.03) and 70.6kcal (p = 0.01), respectively, and daytime drop in serum cortisol level was lessened by 125 mmol/l (p = 0.02) and 45 mmol/l (p = 0.04), respectively. Acute effects of music on BP were dependent on genre-specific popularity. Computer-generated music reduces overall metabolic rate, influences cortisol diurnal rhythm and has acute effects on physiological responses based on genre-preference.